Pretibial myxoedema: a case study of a 49-year-old male - Rajagopalan, Rajesh; Vedhanayagam, Mohankumar; Kandasamy, Revathi; Govindan, Srinivasahan Karattupalayam; Thangavelu, Priyathileepan; K., Sachin Subrahmanya (International Journal of Research in Dermatology, 2025)
Pretibial myxoedema (PTM), also known as thyroid dermopathy, is a rare but distinctive complication of Graves’ disease, often appearing as skin lesions on the shins. A 49-year-old male with thyrotoxicosis and diabetes presented with significant swelling in his lower legs, including the shins, ankles, and feet. Laboratory tests revealed normal thyroid function but elevated thyroid-stimulating hormone (TSH) receptor antibodies, confirming PTM diagnosis upon biopsy. Thyroid dermopathy is usually asymptomatic, but severe cases may result in elephantiasis or thyroid acropachy, often accompanying ophthalmopathy, which typically appears earlier. Diagnosis is made by identifying characteristic lesions in patients with a history of Graves’ disease and ophthalmopathy, sometimes requiring biopsy for confirmation. Though many cases are mild and self-resolving, topical corticosteroids can provide relief in symptomatic or cosmetically concerning cases. In severe instances, systemic immunomodulation may be required, though evidence supporting its long-term efficacy is limited. The underlying pathogenesis involves immune-mediated fibroblast activation and glycosaminoglycan (GAG) production, particularly in the pretibial area due to mechanical factors. Studies show that subclinical dermopathy can occur in untreated Graves’ disease, though histological changes in other areas like the forearm remain rare. Overall, treatment remains largely palliative, with more effective options still needed.